Corrigendum - Corrigendum (Al-Qalam Institute, 2025)
In the article “Harmonization of Customary Law and Islamic Law in the Management of Forbidden Lakes in Village Communities” (Vol. 03 No. 01, 2025: 01–13), the name Dr. Farouq Saber Al-Shibli was incorrectly included as a co-author without his knowledge, contribution, or consent.His name has now been removed from the article PDF, metadata, and indexing.The editorial team sincerely apologizes for this error.